Interaction of gold nanoparticles and nickel(II) sulfate affects dendritic cell maturation. Issue 10 (25th November 2016) - Deville, Sarah; Baré, Birgit; Piella, Jordi; Tirez, Kristof; Hoet, Peter; Monopoli, Marco P.; Dawson, Kenneth A.; Puntes, Victor F.; Nelissen, Inge
Abstract: Despite many investigations have focused on the pristine toxicity of gold nanoparticles (GNPs), little is known about the outcome of co-exposure and interaction of GNPs with heavy metals which can possibly detoxify or potentiate them. Here, the combined exposure of nickel (II) sulfate (NiSO4 ) and GNPs on the maturation response of dendritic cells (DCs) was explored. Exposure to GNPs or NiSO4 separately induced cell activation. When cells were exposed to a mixture of both, however, the observed cell activation pattern indicated a competitive rather than an additive effect of both inducers with levels similar to those induced by NiSO4 alone. Quantification of the GNP uptake by DCs demonstrated a significant decrease in intracellular gold content during co-incubation with NiSO4 . An extensive physiochemical characterization was performed to determine the interaction between GNPs and NiSO4 in the complex physiological media using nanoparticle tracking analyses, disc centrifugation, UV–visible spectroscopy, ICP-MS analyses, zeta potential measurements, electron microscopy, and proteomics. Although GNPs and NiSO4 did not directly interact with each other, the presence of NiSO4 in the physiological media resulted in changes in GNPs' charge and their associated protein corona (content and composition), which may contribute to a decreased cellular uptake of GNPs and sustaining the nickel-induced DC maturation. The presented results provide new insights in the interaction of heavy metals and NPs in complex physiological media. Moreover, this study highlights the necessity of mixture toxicology, since these combined exposures are highly relevant for human subjection to NPs and risk assessment of nanomaterials.